Different characteristics and prognostic impact of deep-vein thrombosis / pulmonary embolism and intraabdominal venous thrombosis in colorectal cancer patients - Choi, Seyoun; Lee, Keun-Wook; Bang, Soo-Mee; Kim, Sujung; Lee, Jeong-Ok; Kim, Yu Jung; Kim, Jee Hyun; Park, Young Soo; Kim, Duck-Woo; Kang, Sung-Bum; Kim, Jae-Sung; Oh, Doyeun; Lee, Jong Seok (Thrombosis and Haemostasis, 2011)
This study was performed to determine the incidence, risk factors, and prognostic implications of venous thromboembolism (VTE) in Asian patients with colorectal cancer (CRC). Differences in clinical characteristics and prognostic impact between extremity venous thrombosis (or deep-vein thrombosis; DVT)/pulmonary embolism (PE) and intra-abdominal venous thrombosis (IVT) were also evaluated. For this study, consecutive CRC patients (N = 2,006) were enrolled and analyses were conducted retrospectively. VTEs were classified into two categories (DVT/PE and IVT). Significant predictors of developing VTEs were advanced stage and an increased number of co-morbidities. The two-year cumulative incidence of DVT/PE was 0.3%, 0.9% and 1.4% in stages 0~1, 2 and 3, respectively; this incidence range of DVT/PE in Asian patients with loco-regional CRC was lower than in Western patients. However, the two-year incidence (6.4%) of DVT/PE in Asian patients with distant metastases was not lower than in Western patients. Although 65.2% of patients with DVT/PE were symptomatic, only 15.7% of patients with IVT were symptomatic. During chemotherapy, DVT/PE developed more frequently than IVT. Only DVT/PE had a negative effect on survival; IVT had no prognostic significance. In conclusion, despite the low incidence of DVT/PE in Asian patients with loco-regional CRC, the protective effect of Asian ethnicity on VTE development disappears as tumour stage increases in patients with distant metastases. Considering different clinical characteristics and prognostic influences between DVT/PE and IVT, the treatment approach should be also different.
Keywords: Venous thromboembolism; colorectal cancer; incidence; prognosis; ethnicity